If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -9 = -9(x + 3) Reorder the terms: -9 + 9x = -9(x + 3) Reorder the terms: -9 + 9x = -9(3 + x) -9 + 9x = (3 * -9 + x * -9) -9 + 9x = (-27 + -9x) Solving -9 + 9x = -27 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -9 + 9x + 9x = -27 + -9x + 9x Combine like terms: 9x + 9x = 18x -9 + 18x = -27 + -9x + 9x Combine like terms: -9x + 9x = 0 -9 + 18x = -27 + 0 -9 + 18x = -27 Add '9' to each side of the equation. -9 + 9 + 18x = -27 + 9 Combine like terms: -9 + 9 = 0 0 + 18x = -27 + 9 18x = -27 + 9 Combine like terms: -27 + 9 = -18 18x = -18 Divide each side by '18'. x = -1 Simplifying x = -1
| (2t-5)(3t-6)=0 | | y=5x+21 | | 4x+4=x+2 | | 2(y+6)(y-8)=0 | | 2x+10=-3x+50 | | 3.14(2x+10.5)= | | 2-7d=-72 | | 1996+43r=7385-67r | | -3(13-2t)=15 | | 3x=8x+35 | | 7(-3+5x)=364 | | -11(11x+8)=34+x | | 3(5+4x)=-69 | | (2x+3y+1)dx+(4x+6y+1)dy=0 | | 9x+81=x-7 | | 2(2-7x)=4 | | -5(-7-7v)=35+8v | | -2x^2+0x+18=0 | | 7(5x-10)=140 | | -8+3x=-24+9x | | 3(-3x+9)=-54 | | 5(1X-7)=-50 | | -2(m-30)=-6mk | | 31-6x=11-10x | | -7(4+x)=49 | | -7(8x+4)=5x-28 | | 2xy-13xy= | | -3a+2=3a+14 | | x-2y=0.9 | | 9x-21=6x+30 | | 3(-6x-7)=159 | | 8.9(.04213)-.25= |